CRITICAL SUCCESS FACTORS DALAM PENGELOLAAN DATA SISTEM INFORMASI AKUNTANSI - Djaja Perdana (Akademi Akuntansi YKPN Yogyakarta, 2009)
This research aims to investigate the critical success factors influence to level of maturity and performance of data management in CV Wirotomo Trading, Yogyakarta. The research focused on data management of accounting information system including in delivery and support domain by controlling implementation, level of maturity measurement, and performance indicators evaluation with COBIT critical success factors as standard. The research tools is an adoption result from COBIT Implementation Tool Set, COBIT Control Objectives, Maturity Model, and Key Performance Indicators that adapted into subject’s organization environment. Data collecting method used the documents inspection, interview and self-assessment questionnaire for selected subjects. The result shows that the level of maturity and performance indicators of data management keep increasing after the critical success factors based controlling is implemented.Keywords: COBIT Framework, Level of Maturity, Key Performance Indicators, Critical Success Factors, accounting information system